Phytotoxic activity of sunflower leaf extracts in combination with pretilachlor on barnyardgrass (Echinochloa crus-galli) in direct-seeded rice - Dilipkumar Masilamany (Terengganu: Universiti Malaysia Terengganu, 2012)
The increasing use of synthetic chemicals for pest control in rice has become overwhelming economical border; and more important, it could pose a serious threat of the public health and of the environment. In addition, the extensive use of synthetic herbicides has been the cause for the evolution of herbicide-resistant bamyardgrass {Echinochloa crus-galli) worldwide. This weed species is the most competitive weed in rice after the weedy rice (Oryza sativa).